Synthesis of 2,3-dihydroquinazoline -4(H)-one Derivatives by Intramolecular Oxidative Coupling Reaction as Cytotoxic Agent. - Farjana Akter Himo; Md. Awlad Hossain; Md. Farid Uddin; Koushik Saha (Journal of Science, 2026)
A series of 2,3-dihydroquinazoline-4(H)-ones derivatives having fused with 9,10- dihydrophenanthrene were prepared by a three component condensation reaction of isatoic anhydride, primary amines and aromatic aldehydes followed by the intramolecular oxidative coupling reaction in the presence of nontoxic FeCl3. This reaction involves dehydrogenative coupling of a various of 1,2-diarylethylene derivatives at temperature 0-5 oC. NMR and IR spectroscopy were used to characterize all the synthesized compounds and studied their cytotoxic property by Brine Shrimp Lethality Bioassay. Among these compounds, compound 2b and 3b showed moderate cytotoxicity with LC50 values 76.16 and 70.70 µg/ml respectively.